Social Media as Narrative Pedagogy: Instagram Stories and TikTok in Contemporary Learning Practices - Misbahul Khairani; Aung Myint; Thandar Htwe; Siti Nur Azizah (Yayasan Adra Karima Hubbi, 2025)
Background. The rapid evolution of social media platforms has reshaped educational communication, offering new spaces for narrative-based learning that merges visual storytelling with participatory engagement. Purpose. This study explores the use of Instagram Stories and TikTok as narrative pedagogical tools that enhance students’ reflective, creative, and critical learning experiences in contemporary classrooms. Method. The research aims to analyze how short-form digital narratives can foster multimodal literacy, social interaction, and emotional connection in learning processes. Employing a qualitative narrative inquiry design, data were collected through classroom observations, student-generated content, and semi-structured interviews with educators and learners across higher education contexts. Results. The findings reveal that Instagram and TikTok stories serve as dynamic platforms for constructing personalized learning narratives that integrate academic content with lived experiences. Students demonstrated heightened engagement, creativity, and agency when invited to design educational stories, while teachers reported improved dialogic relationships and inclusivity in their classrooms. Conclusion. The study concludes that narrative pedagogy through social media transforms passive consumption into active knowledge creation, bridging formal and informal learning spaces. It emphasizes the potential of digital storytelling to cultivate critical digital citizenship and empathy among learners in the 21st century.